2009
DOI: 10.1143/jjap.48.016003
|View full text |Cite
|
Sign up to set email alerts
|

Fast Gas Replacement in Plasma Process Chamber by Improving Gas Flow Pattern

Abstract: The precise and high-speed alteration of various gas species is important for realizing precise and well-controlled multiprocesses in a single plasma process chamber with high throughput. The gas replacement times in the replacement of N 2 by Ar and that of H 2 by Ar are measured in a microwave excited high-density and low electron-temperature plasma process chamber at various working pressures and gas flow rates, incorporating a new gas flow control system, which can avoid overshoot of the gas pressure in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…At the same time, it was reported that gas replacement time becomes shorter with the introduction of an upper shower plate that can supply gases with a uniform down flow pattern in the chamber compared with the case that gas is only introduced from the sidewall of the chamber, demonstrating that gas replacement characteristics depend on the gas supply method used. 3) It is newly found that such characteristic variations induce a deviation in the actual time variation of gas pressure from the solution of the differential equation of gas flow, contrary to our previous study. 2) Thus, the establishment of a design guide for obtaining an optimum pulse size in the pulse-controlled gas injection method that can be applied to arbitrary gas flow patterns in various chambers is strongly required.…”
Section: Introductioncontrasting
confidence: 81%
See 3 more Smart Citations
“…At the same time, it was reported that gas replacement time becomes shorter with the introduction of an upper shower plate that can supply gases with a uniform down flow pattern in the chamber compared with the case that gas is only introduced from the sidewall of the chamber, demonstrating that gas replacement characteristics depend on the gas supply method used. 3) It is newly found that such characteristic variations induce a deviation in the actual time variation of gas pressure from the solution of the differential equation of gas flow, contrary to our previous study. 2) Thus, the establishment of a design guide for obtaining an optimum pulse size in the pulse-controlled gas injection method that can be applied to arbitrary gas flow patterns in various chambers is strongly required.…”
Section: Introductioncontrasting
confidence: 81%
“…Time variations of relative concentrations of these gases in the chamber during the plasma excitation including the transient period of the gas replacement were approximately estimated by optical emission spectroscopy (OES) using the calibration curves. 2,3) In the OES measurement, an optical fiber was set outside of a quartz window installed at the chamber wall, and the emitted light was guided to the optical spectrometer (Ocean Optics HR2000) through the optical fiber, as shown in Fig. 1.…”
Section: Optical Emission Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…During the dielectric formation process, gas flow control is an important factor that influences the concentration of process gas and the pressure of the process chamber (8)(9)(10)(11)(12). Additionally, controlling the gas flow accurately makes process costs lower, because the minimum necessary source gas is used at each cycle of ALD.…”
Section: Introductionmentioning
confidence: 99%